Chemical Composition of Cashewnut Shells - Ingle, T. R.; Mahajan, M. B. (Indian Forester, 1972)
Two samples of oil-free cashewnut shells from natural cashewnuts (Indian&African varieties) and three samples of spent cashewout shells from different cashew industries have been analysed for their different constituents. The analytical results of all samples indicate that the composition of cashewnut shells as well as tbe nature of Î±-cellulose, has not been changed to a significant extent during processing.